Real‐Time Assessment of Granule Densification in High Shear Wet Granulation and Application to Scale‐up of a Placebo and a Brivanib Alaninate Formulation. Issue 3 (2nd December 2014) - Narang, Ajit S.; Sheverev, Valery A.; Stepaniuk, Vadim; Badawy, Sherif; Stevens, Tim; Macias, Kevin; Wolf, Avi; Pandey, Preetanshu; Bindra, Dilbir; Varia, Sailesh
<x xml:space="preserve">Abstract</x> Real‐time monitoring and control of high shear wet granulation (HSWG) using process analytical technologies is crucial to process design, scale‐up, and reproducible manufacture. Although significant progress has been made in real‐time measurement of granule size distribution using focused beam reflectance measurement (FBRM), real‐time in‐line assessment of granule densification remains challenging. In this study, a drag force flow (DFF) sensor was developed and used to probe wet mass consistency in real‐time. In addition, responses from FBRM and DFF sensors were compared to assess complementarity of information on granulation progress from the two probes. A placebo and a brivanib alaninate formulation were granulated with different concentrations of binder or water, respectively, while measuring granule size growth, densification, and DFF sensor response. The DFF sensor was able to quantitatively characterize with high resolution a response of wet mass consistency distinct from granule size distribution. The wet mass consistency parameter correlated well with granule densification, which was shown as a critical material attribute that correlated with tablet dissolution. In addition, application of DFF sensor to scale‐up of granulation was demonstrated. These results showed the value of wet mass consistency measurement using DFF for WG monitoring and control. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:1019–1034, 2015